2016
DOI: 10.1007/s11325-016-1397-x
|View full text |Cite
|
Sign up to set email alerts
|

Positional therapy in patients with residual positional obstructive sleep apnea after upper airway surgery

Abstract: The results of this study indicate that additional PT in a complex OSA patient population with residual POSA after surgery can increase overall therapeutic effectiveness by improving the median MDA from 39.5 % (effect of surgery alone) to 65.6 % (effect of combining surgery and PT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…In a prospective single arm study from Netherlands of 36 patients with mild to moderate POSA by van Maanen et al , a very high treatment adherence rate (defined by >4 hours device use/day) of 92.7% with the Nightbalance SPT was observed 16. In another two studies using the Nightbalance SPT by Benoist et al , treatment adherence (defined as >4 hours device use/day at least 5 days in a week) was found to be 89.3%22 and 89.0%,23 respectively at 3 months. The much lower PT adherence rate seen in our Asian study population reinforces the importance of replicating positive results from Caucasian studies in other ethnic populations.…”
Section: Discussionmentioning
confidence: 94%
“…In a prospective single arm study from Netherlands of 36 patients with mild to moderate POSA by van Maanen et al , a very high treatment adherence rate (defined by >4 hours device use/day) of 92.7% with the Nightbalance SPT was observed 16. In another two studies using the Nightbalance SPT by Benoist et al , treatment adherence (defined as >4 hours device use/day at least 5 days in a week) was found to be 89.3%22 and 89.0%,23 respectively at 3 months. The much lower PT adherence rate seen in our Asian study population reinforces the importance of replicating positive results from Caucasian studies in other ethnic populations.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, patients suffering from residual POSA under a given therapy can be good candidates for combination therapy. Dieltjens et al 26 studied the effect of the combination of OA therapy with SPT, whereas Benoist et al 27 investigated the effect of additional SPT therapy after upper airway surgery. Both studies showed promising results.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25] Furthermore, the use of the chest-worn sleep position trainer (SPT) was studied as part of combination therapy in patients who have residual POSA after treatment with oral appliances (OA) or after upper airway surgery. 26,27 The authors of both studies concluded that additional positional training in a group of patients with residual POSA after standard treatment can increase the overall therapeutic effectiveness.…”
Section: Evaluation Of a Trial Period With A Sleep Position Trainer Imentioning
confidence: 99%
“…In positional patients, in particular, performing DISE in both the lateral and supine position can be of added value, especially since the role of positional therapy is gaining momentum, both as a single treatment option, or as combination therapy, for example, with OAT or upper airway surgery . Various studies have shown that DISE findings in these patients differ when performed in the supine or lateral position .…”
Section: Patient Positioning Basic and Special Diagnostic Manoeuvrementioning
confidence: 99%